PULMONARY EMBOLISM THROMBOLYSIS (Неотложная медицинская помощь)
Источник: Meyer G., Vicaut E., Danays T., et al. Fibrinolysis for Patients with Intermediate-Risk Pulmonary Embolism // N. Engl. J. Med. – 2014. – Vol. 370. – P. 1402–1411.